Information structure of subordinate clauses in Miriwoong - Sim, Michelle Jia En (2019)
This study aims to investigate subordinate clauses in Miriwoong, an Australian aboriginal language in Kununurra, Western Australia, about which there is a salient research gap regarding clause structure. Miriwoong, similar to other Australian aboriginal languages, exhibits properties of “non-configurationality”, which refers to having free word order and syntactically discontinuous expressions (Austin & Bresnan, 1996: 215). This project hence deviates from a structural perspective, analysing subordinate clauses through information structure, using Lambrecht’s (1994) framework. To fill the gap in Miriwoong literature, this paper covers additional ground, such as structure in simple and paratactic clauses, and other features hypothesised as relevant to focus structure in subordinate clauses. The research mainly utilised interlinearised transcriptions of past recordings collected at Mirima Dawang Woorlab-gerring, neglecting prosodic features, which is ground for future research. Overall, it was found that Miriwoong is a focus-final language (i.e. new information is placed sentence-finally), while focus-initial utterances were marked. Adverbial and relative clauses in Miriwoong take the form of adjoined clauses similar to those described in Hale (1976). However, relative clauses in Miriwoong are usually sentence-final and immediately follow the head noun, which resembles Wambaya (Nordlinger, 2006) more than Warlpiri (Hale, 1976). Adverbial clauses were predominantly sentence-initial and non-focal. Finally, paratactic clauses were found to 1) express sequential events or 2) draw a relation between two observations.